Hypersomnia in Whipple disease: case report Hipersónia na doença de Whipple: relato de caso - Luís F. Maia; Mónica Marta; Vitor Lopes; Nelson Rocha; Carlos Lopes; Antônio Martins-da-Silva; Luís Monteiro (Arquivos de Neuro-Psiquiatria)
Whipple disease (WD) is a rare systemic infection caused by Tropheryma whippelii. Neurological involvement has been recognised in 40% of patients, either as initial manifestations or during the course of the disease. We report on a 45 years-old man with WD with initial, persistent and irresistible episodes of daytime somnolence. The patient was HLA-DQB1*0602 positive (genetic marker for narcolepsy). WD diagnosis was suspected on clinical and MRI basis and confirmed by histological and immunohistochemical study of duodenal biopsy. Forty months later all clinical features improved, narcoleptic-like episodes disappeared and cerebral MRI and CSF normalised. Longitudinal neurophysiological studies revealed persistent sleep pattern abnormalities with sleep fragmentation, paucity of slow wave and of REM sleep. The disruption of the hypocretin circuitry in the hypothalamic - diencephalic region triggered by the infection was the probable cause of the hypersomnia and narcopleptic symptoms. WD should be added to the list of causes of secondary hypersomnia. A doença de Whipple (DW) é infecção sistémica rara causada pelo Tropheryma whippelii. Cerca de 40% dos doentes apresentam envolvimento neurológico, seja como manifestação inicial da doença, seja durante o seu curso. Apresentamos o caso de um homem de 45 anos com doença de DW com episódios iniciais, persistentes e irresistíveis de sonolência durante a actividade diurna. O doente era positivo para o HLA-DQB1*0602 (marcador genético de narcolepsia). A suspeita do diagnóstico de DW foi levantada com base na clínica e RM e confirmada por estudo imunocitoquímico do material de biópsia jejunal. Quarenta meses mais tarde, todas as manifestações clínicas melhoraram, os episódios narcolépticos desapareceram, e a RM e o LCR normalizaram. Os estudos neurofisiológicos seriados do sono revelaram alterações persistentes caracterizadas por fragmentação do sono, escassez de ondas lentas e sono REM. A perturbação do circuito da hipocretina na região hipotálamo-diencefálica, causada pela infecção, foi a causa provável da hipersónia num doente geneticamente susceptível. A DW deve ser incluída nas causas de hipersónia secundária.